2005
DOI: 10.1097/01.shk.0000180625.53800.63
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethyl Starch Inhibits Neutrophil Adhesion and Transendothelial Migration

Abstract: A resuscitation strategy that significantly alters the state of neutrophil (PMN) activation may impact organ function and survivability after shock. Various resuscitative fluids have been shown to elicit a severe immune activation and an upregulation of cellular injury markers, whereas other fluids have been shown to be protective. Recent studies have demonstrated that hydroxyethyl starch (HES), an artificial colloid, may exert significant anti-inflammatory effects, whereas conflicting studies with the same su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 34 publications
3
24
2
1
Order By: Relevance
“…In addition, investigation of adverse side effects (i.e., impairment of blood coagulation) of high-and low-molecular-weight low-substituted HES solutions in further clinical settings (acute vs. chronic vs. repetitive administration) are desirable to evaluate their clinical utility. Besides the extensively described volume restoring properties, HES seems to exert significant beneficial antiinflammatory effects, 34,35 such as a diminishment of polymorphonuclear neutrophil sequestration in multiple organs. 34,36 Recent studies have shown that the clinically relevant effect of HES on leukocyte sequestration depends on the regulation of the integrin function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, investigation of adverse side effects (i.e., impairment of blood coagulation) of high-and low-molecular-weight low-substituted HES solutions in further clinical settings (acute vs. chronic vs. repetitive administration) are desirable to evaluate their clinical utility. Besides the extensively described volume restoring properties, HES seems to exert significant beneficial antiinflammatory effects, 34,35 such as a diminishment of polymorphonuclear neutrophil sequestration in multiple organs. 34,36 Recent studies have shown that the clinically relevant effect of HES on leukocyte sequestration depends on the regulation of the integrin function.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the extensively described volume restoring properties, HES seems to exert significant beneficial antiinflammatory effects, 34,35 such as a diminishment of polymorphonuclear neutrophil sequestration in multiple organs. 34,36 Recent studies have shown that the clinically relevant effect of HES on leukocyte sequestration depends on the regulation of the integrin function. 36 The duration of the antiinflammatory effect after HES administration thus may be largely determined by the intravascular elimination of the colloid.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][24][25][26][27][28][29] We shared the commonly held perception that both volume effect and molecule characteristics are among the most important factors in organ protection; however, the current study demonstrated that the HES molecule plays a role in hepatoprotection against reperfusion injury. The infused volume of HES solution (13 mLÁkg -1 ) adjusted to the weight of the rats was within the doses reported for volume repletion in clinical studies.…”
Section: Discussionmentioning
confidence: 74%
“…[7][8][9][10][11][12][13] Best known for their use as intravascular volume expanders, HES solutions are also associated with microcirculatory improvement and antiinflammatory properties. [14][15][16][17][18] Despite their adverse effects in other settings, namely, on renal function, coagulation, and tissue storage, it was suggested previously that the older high molecular weight HES can reduce the deleterious effect of IRI. 14,19 Distinct types of HES show clear differences in pharmacokinetic, clinical efficacy, and adverse effects.…”
Section: Résumémentioning
confidence: 99%
“…While mannitol is considered an inert substance, recent research has suggested possible interdependencies with monocyte and neutrophil function (upregulation of HLA-DR in monocytes, upregulation of CD11b in neutrophils and monocytes, and inhibition of neutrophil apoptosis (Turina et al, 2008)). Hydroxyethyl starch (Handrigan et al, 2005;Matharu et al, 2008) and cellulose (Hänsch et al, 1996;Moore et al, 2001;Bae et al, 2004;Ewoldt et al, 2004;Hernández et al, 2004Hernández et al, , 2009 have also both been shown to alter inflammatory responses due to their different effects on neutrophils. While glucose is also able to support the maintenance of oncotic pressure (Hicks et al, 2006), it supports the specimen's metabolism and survival.…”
Section: Cell Free Solutionsmentioning
confidence: 99%